THE MONTHLY VARIATIONS OF DISCHARGE AND EFFECT THAT ON A TOTAL DISSOLVE SUSPENDED AND SALINITY IN SHATT AL-ARAB RIVER (South of Iraq). - Al- Mahmood, H. (Iraqi Journal of Science, 2024)
The aim of this study is to explain the role of the discharge of Shatt Al-Arab River , two water years have been chosen to show this effect (2006 & 2007) to know the Effect of discharge on total dissolve suspended and salinity variations in (Al-Sallow section) which show all river‘s efficacious from dawn stream and up stream .The results display that the flood discharge is high in comparison with ebb discharge, (T.D.S) and salinity is a high in comparison with last studies, and there was a difference between the phase of flood and ebb, reason of the marine and river sources, another difference(yearly-monthly) in these characteristics because of effect Water Balance from river sources of Shatt Al-Arab River and due to terminate the rule of Ahwar region as a settlement basin of Tigris and Euphrates sediments loads. in addition to that the progress of Salt Wedge procession in Shatt Al-Arab from Arabian Gulf with shortage discharge